(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
This thesis provides a comprehensive analysis of the complex interplay between the human immune system and SARS-CoV-2, the virus responsible for the COVID-19 pandemic. The central objective is to synthesize the critical immunological lessons learned from this global health crisis, focusing on the dual nature of the immune response: its essential role in viral clearance and recovery, and its potential to cause severe immunopathology. Additionally, it explores the phenomena of waning immunity, viral immune evasion, and the implications of emerging variants. By integrating findings from virology, clinical immunology, and vaccinology, this work concludes that the COVID-19 pandemic has served as a monumental real-world experiment, profoundly advancing our understanding of antiviral immunity and reshaping paradigms for future pandemic preparedness, therapeutic design, and global public health strategy.